Fiscal Policy in Pakistan Since 1970. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1992)
The analysis in this paper suggests that the large fiscal deficits that Pakistan has experienced over most of the period since 1970 led to some crowding out of private investment, resulting in slower output growth than would otherwise have been observed. Past fiscal deficits have also resulted in a substantial accumulation of domestic and external debt. In addition, the possibilities for currency substitution that have been created by the removal of restrictions on capital flows from Pakistan, as well as on foreign currency holdings of domestic residents, may have limited the potential for collecting the inflation tax. Accordingly, continued effort is likely to be needed to attain a fiscal position that is sustainable over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet